Congenital hypomyelinating neuropathy. Issue 12 (December 1985) - Harati, Y; Butler, I J
Abstract : Two patients with congenital hypomyelinating neuropathy are reported with details of sural nerve pathology. The resemblance of this condition to the hypomyelinating neuropathy of Trembler mice is discussed and the pertinent medical literature reviewed.